ENVIRONMENTAL MANAGEMENT, TYPES AND OBJECTIVES (American Journal of Interdisciplinary Research and Development, 2022)
Environmental management is a component of the overall corporate governance system aimed at achieving the goals specified in the environmental policy. The following article is devoted to the study of environmental management and its main tasks and objectives.